Silymarin-choline combination versus ursodeoxycholic acid in non-alcoholic fatty liver disease: A randomized double-blind clinical trial - Chakrabarty, Purba; Mukherjee, Mayukh; Adhikary, Rajasee; Shatavisa Mukherjee,; Majumder, Souvik; Sarkar, Dipak Kumar; Ghosh, Saubhik (Asian Journal of Medical Sciences, 2024)
Background: Non-alcoholic fatty liver disease (NAFLD) is an influential cause of liver disease burden. However, there is no evidence-based standard of care. Considering that oxidative stress and diet deficiency of choline plays a role in the pathophysiology of hepatic damage, natural compounds such as silymarin, choline, and ursodeoxycholic acid (UDCA) represent popular therapeutic options. Aims and Objectives: The present study aimed to compare the efficacy, safety, and adherence of the silymarin-choline combination and UDCA in patients with NAFLD. Materials and Methods: A double-blind parallel arm study where 88 NAFLD-diagnosed patients were randomized to receive either silymarin-choline bitartrate or UDCA for 6 months, along with lifestyle modification recommendations. Weight, body mass index, liver enzyme levels, lipid profile parameters, homeostatic model assessment of insulin resistance, liver stiffness measurement, and liver biopsy were monitored at baseline and 6 months. Adverse events and adherence were monitored. Results: A total of 39 patients received a tablet of silymarin-choline bitartrate, while 40 received UDCA. A significant improvement was observed in aspartate aminotransferase (U/L) levels from 54.18 (17.02) to 37.23 (9.94) (P=0.000), NAFLD activity score from 6.5 (0.37) to 2.7 (1.26) (P=0.000), and transient elastography (kilopascal) scores, more in patients receiving the silymarin-choline combination, whereas for those receiving UDCA, a significant improvement was observed in total cholesterol (mg/dL) from 187.88 (27.49) to 171.45 (28.47) (P=0.000) and low-density lipoprotein levels. No major safety issues were observed in both groups. Conclusion: NAFLD is currently treated by treating associated comorbidities, which cannot always stop its progression. Silymarin-choline bitartrate can be used as a better alternative to UDCA for the treatment of NAFLD.